Dictating Phenotype, Function, and Fate of Human T Cells with Co‐Stimulatory Antibodies Presented by Filamentous Immune Cell Mimics. Issue 4 (16th February 2022) - Schluck, Marjolein; Eggermont, Loek J.; Weiden, Jorieke; Popelier, Carlijn; Weiss, Lea; Pilzecker, Bas; Kolder, Sigrid; Heinemans, Anne; Rodriguez Mogeda, Carla; Verdoes, Martijn; Figdor, Carl G.; Hammink, Roel
Abstract: T cells require a co‐stimulatory signal in addition to T‐cell receptor (TCR) stimulation to achieve full activation. While most studies focus on the co‐stimulatory receptor CD28, little is known about the role of the other co‐stimulatory receptors in T‐cell signaling. A deeper understanding of how co‐stimulatory receptor signaling cooperates with TCR signaling could improve the ability to control T‐cell function and benefit the design of T‐cell based immunotherapies. Artificial antigen presenting cells (aAPCs) enable tight control over the signals given to T cells. In this study, filamentous polyisocyanopeptide (PIC) polymers (immunofilaments) are used as nanosized aAPCs to study the role of the engagement of six distinct co‐stimulatory molecules on human T‐cell phenotype, function, and fate in the context of TCR signaling. The immunofilaments highlight important roles for CD28 and CD2 signaling in T‐cell priming, proliferation, cytokine production, and multifunctionality. Taken together, this work provides insight into the role of combined TCR and co‐stimulation on T‐cell phenotype, function, and fate using immunofilaments. Notably, the findings on the roles of co‐stimulatory molecule function can be used for the rational design of future cancer immunotherapies. Abstract : Co‐stimulation is the key to full‐blown T‐cell activation. Filamentous shaped artificial antigen‐presenting cells offer a unique opportunity to directly study the role of combined T‐cell receptor (TCR) and co‐stimulatory receptor stimulation. The phenotype, function, and fate of human T cells after in vitro stimulation are mostly influenced with αCD28 and αCD2 co‐stimulation.